Development of Augmented Reality Technology Based Learning Media of Lathe Machines - Agus Suryanto; Diah Ayu Kusumawati; Ibrahim M. H. Sanhoury (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Conventionally, in the learning process teachers usually explain lathe machines using only one unit machine thus the students cannot observe and learn the machine comprehensively. Hence, it is necessary to create learning media based on Augmented Reality technology that can be individually accessed with smartphone devices to facilitate the students in examining the lathe parts in detail with ease. This study discusses the development of Augmented Reality technology based learning media to display parts of the lathe in informative details. This study was categorized as Research and Development. The procedure of the study consisted of several stages including finding potential and problem, literature studies, product development, expert validation, product revisions, product trial, product revision, user response, product revision and final product development. The results showed that the developed learning media was applicable. The percentages of product testing and user response testing were 87.50% and 82% respectively which both were categorized as good.